The Application of Structural Equation Modeling in the Investigation of Factors Affecting the Dental Caries Index of Children - Reza Shahi; Elnaz Shafiei; Khadijeh Pooyandeh; Sana Ahrabi (مجله دانشکده دندانپزشکی اصفهان)
Structural equation modeling is a class of multivariate statistical methods that combines the dimensions of factor analysis and regression to enable researchers to simultaneously examine the relationships betweenvariables. This method has not been used in dental research until now. The purpose of this article is to determine the effect of parents' knowledge, attitude, and performance on their children's dental caries with the mediation of sugar consumption using this method.Materials & Methods:In this analytical observational study, questionnaires of parents' knowledge, attitude, and performance were completed among 385 people of Tabriz city in February and March 2023. These questionnaires are based on previous research and made by researchers. Partial Least Square with Structural Equation Modeling was used to test the research hypotheses (α = 0.01).Results:According to the results of statistical analysis, the effect of "parental awareness", "parental performance" and "children's consumption of sugary substances" on "tooth decay index" and also the effect of "parental awareness", "parental attitude" and "parental performance" on " The consumption of sugary substances by children" is significant at the level of 0.01 (p value < 0.01). Also, the results of the analysis showed that the indirect effect of the variables "awareness", "attitude" and "performance" of the parents on the variable "decay index of primary teeth" through the mediator variable "amount of consumption of sugary substances" is significant at the level of 0.01 (p value < 0.01). However the effect of "parental attitude" on "tooth decay index" was not significant (p value > 0.05).Conclusion:In this study, it was shown that the knowledge, attitude and performance of parents have a significant effect on the tooth decay index through the variable of consumption of sugary substances